2016
DOI: 10.1021/acsami.6b03569
|View full text |Cite
|
Sign up to set email alerts
|

Pseudocapacitive Properties of Two-Dimensional Surface Vanadia Phases Formed Spontaneously on Titania

Abstract: Pseudocapacitive properties of V2O5-based adsorbates supported on TiO2 nanoparticles, which form spontaneously as two-dimensional (2-D) nonautonomous surface phases (complexions) at thermodynamic equilibria, have been systematically measured. Surprisingly, surface amorphous films (SAFs), which form naturally at thermodynamic equilibria at 550-600 °C with self-regulating or "equilibrium" thicknesses on the order of 1 nm, exhibit superior electrochemical performance at moderate and high scan rates (20-500 mV/s) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…However, in our cases, the densities of sintered specimens with different atomic concentrations of divalent dopants were all about 90% of theoretical density; thus, the improvements in grain boundary conductivity cannot be simply attributed to improved densities. In addition, our EDS results and calculated dopant formation energies suggest that dopants are more likely to be incorporated in a secondary phase at grain boundaries, such as [47,48], pseudocapacitors [49] and a similar surface phase was recently found to improve the oxygen ionic conductivity of nanofibers by more than 1000 times [50], see a recent review for relevant discussion [51]. Unfortunately, these NASICON materials are extremely sensitive to electron and ion beams, preventing us from conducting direct atomicresolution characterization of grain boundaries (as the MRSICON specimens, particularly their grain boundaries, can be damaged by the high-energy electron beam in TEM or even in high-magnification SEM).…”
Section: Discussionmentioning
confidence: 77%
“…However, in our cases, the densities of sintered specimens with different atomic concentrations of divalent dopants were all about 90% of theoretical density; thus, the improvements in grain boundary conductivity cannot be simply attributed to improved densities. In addition, our EDS results and calculated dopant formation energies suggest that dopants are more likely to be incorporated in a secondary phase at grain boundaries, such as [47,48], pseudocapacitors [49] and a similar surface phase was recently found to improve the oxygen ionic conductivity of nanofibers by more than 1000 times [50], see a recent review for relevant discussion [51]. Unfortunately, these NASICON materials are extremely sensitive to electron and ion beams, preventing us from conducting direct atomicresolution characterization of grain boundaries (as the MRSICON specimens, particularly their grain boundaries, can be damaged by the high-energy electron beam in TEM or even in high-magnification SEM).…”
Section: Discussionmentioning
confidence: 77%
“…In a broader context, this study has demonstrated the anisotropic surface segregation (or formation of 2D surface phases in general) can be utilized as a facile method to control the particle morphology thermodynamically, as well as modify surface properties (i.e., increase the electrochemical stability and surface transport rates in this particular case), to significantly improve the rate capability, cycling stability, and potentially other properties of battery materials, as well as a broad range of other functional materials for energy-related applications, such as supercapacitors and photocatalysts. , …”
Section: Discussionmentioning
confidence: 99%
“…Annealing at higher temperatures (>500 °C) leads to self‐regulating or “equilibrium” thicknesses ∼1 nm 2D V 2 O 5 surfaces with decreased surface area (by 20–37 %) which however, exhibited improved specific capacitances per unit active material at all rates. Electrochemical impedance analysis explained that former sample showed highest charge transfer resistance than the latter which in turn is correlated with the sample surface area, conductivity and hence the specific capacitance of the active material . Thus, it is clear that optimization of the important parameters‐ active surface area, porosity, conductivity, electrode/electrolyte interface, ion diffusion pathways is very crucial for attaining desired electrochemical signature.…”
Section: Introductionmentioning
confidence: 99%